TERAPI PERMAINAN TRADISIONAL CONGKLAK TERHADAP PENINGKATAN FUNGSI KOGNITIF LANSIA DI DESA ALASSUMUR BESUK : The Effect of Brain Stimulation Therapy through the Traditional Congklak Game on Cognitive Function in the Elderly: A Quasi-Experimental Study in Alassumur Village, Besuk - nur hafifah, vivin; Amilia , Elok; Putri Wandasari , Eka Meyliana (Jurnal Ilmiah Pamenang, 2025)
Lansia merupakan kelompok usia yang rentan terhadap penurunan fungsi kognitif, yang dapat mempengaruhi kualitas hidup mereka. Peningkatan jumlah lansia di Indonesia, termasuk di Kabupaten Probolinggo, menyebabkan kebutuhan akan intervensi untuk menjaga dan meningkatkan fungsi kognitif lansia semakin mendesak. Salah satu intervensi yang menjanjikan adalah terapi stimulasi otak melalui permainan tradisional congklak, yang dapat merangsang fungsi kognitif melalui aktivitas yang melibatkan konsentrasi, perhitungan, dan koordinasi. Penelitian ini bertujuan untuk menguji pengaruh terapi stimulasi otak menggunakan permainan congklak terhadap peningkatan fungsi kognitif lansia di Desa Alassumur Kecamatan Besuk. Desain penelitian menggunakan quasi eksperimen dengan pendekatan pretest-posttest tanpa kelompok kontrol, melibatkan 30 lansia di Desa Besuk yang dipilih dengan teknik total sampling. Intervensi dilakukan selama empat minggu, dua kali per minggu. Fungsi kognitif diukur menggunakan MMSE dan dianalisis dengan uji Wilcoxon. Prosedur dalam penelitian ini adalah perlakuan permainan congklak  yang dilakukan 2 kali dalam seminggu, kegiatan lamanya terapi aalah 30 menit. Hasil uji statistik di dapatkan sign = 0.000 menunjukkan peningkatan fungsi kognitif yang signifikan setelah intervensi (p < 0,05). Terapi permainan congklak terbukti efektif meningkatkan fungsi kognitif dan dapat menjadi alternatif intervensi berbasis budaya lokal bagi lansia. Kesimpulan adalah ada pengaruh Terapi Permainan Tradisional Congklak terhadap Peningkatan Fungsi Kognitif Lansia Di Desa Alassumur Besuk Abstract Older adults are a vulnerable age group prone to cognitive decline, which can affect their quality of life. The increasing number of elderly people in Indonesia, including in Probolinggo Regency, has led to a growing need for interventions aimed at maintaining and improving cognitive function in this population. One promising intervention is brain stimulation therapy through the traditional game of congklak, which can stimulate cognitive function through activities involving concentration, calculation, and coordination.This study aims to examine the effect of brain stimulation therapy using the congklak game on improving cognitive function in older adults in Alassumur Village, Besuk District. The study employed a quasi-experimental design with a pretest-posttest approach without a control group, involving 30 elderly participants from Besuk Village selected using total sampling. The intervention was conducted over four weeks, twice a week. Cognitive function was measured using the Mini-Mental State Examination (MMSE) and analyzed using the Wilcoxon test. The intervention consisted of congklak game sessions conducted twice a week, with each session lasting 30 minutes.The statistical test result showed a significance value of 0.000, indicating a significant improvement in cognitive function after the intervention (p < 0.05). The congklak game therapy was proven effective in enhancing cognitive function and can serve as a culturally based alternative intervention for the elderly. The conclusion of this study indicates that there is a significant effect of traditional congklak game therapy on improving cognitive function in the elderly in Alassumur Village, Besuk. This therapy is effective in stimulating cognitive aspects such as memory, concentration, attention, and numeracy skills, making it a simple and enjoyable non-pharmacological intervention to help maintain and enhance cognitive function in the elderly